Notopterygium incisum as a source of valuable plant substances from traditional Chinese medicine - review of active components, biological activity and botanical aspects from a phytopharmaceutical perspective - Marta Jagiełło; Anna Marchelak; Monika Anna Olszewska; Anna Magiera (Polish Pharmaceutical Society, 2023)
Notopterygium incisum K.C.Ting ex H.T.Chang is a perennial herbaceous plant representing the family Apiaceae. Its natural range mainly covers the north-western, south-western and central parts of China (Gansu, Sichuan, Qinghai and Xizang provinces), as well as the north-eastern part of Tibet. The species provides several herbal medicinal substances (root, rhizome, herb) that have been used in traditional Chinese, Korean and Japanese medicine for centuries. Plant materials obtained from Notoptergium incisum (especially the aromatic root and rhizome) are usually included in complex herbal preparations for internal use used as analgesics, anti-rheumatic, anti-inflammatory and antipyretic agents. The main therapeutic indications for using such preparations are the treatment of rheumatoid arthritis, headache or cold conditions with chills. In recent years, numerous phytochemical and pharmacological studies have been conducted to verify and establish the molecular mechanisms of the activity of Notopterygium incisum and active compounds contained in the relevant plant substances. As a result, their multidirectional biological potential has been documented, especially their potent anti-inflammatory, anti-arthritic and antioxidant activity, followed by some hepatoprotective, antibacterial and anti-cancer effects. Importantly, this species has been introduced into the official European medicine - a monograph of the root and rhizome of Notoptergium incisum (Notopterygii rhizoma et radix) has been included in one of the latest supplements to the European Pharmacopoeia (Supplement 10.7), which also contains several other plant medicinal substances of traditional Far Eastern medicine, underestimated and not used in Europe yet. This report aims to present the current state of knowledge about the species Notopterygium incisum, including botanical aspects, chemical composition and pharmacological data of plant substances and active compounds obtained from the title medicinal plant.